UTILIZATION OF ARTIFICIAL INTELLIGENCE FOR SUSTAINABLE BUILDING ARCHITECTURE - Widodo, Stephanie; Susan, Susan (Universitas Ciputra Surabaya, 2024)
The rise of artificial intelligence (AI) presents a transformative opportunity for architects seeking to achieve sustainable design goals. AI’s ability to extract and analyze vast amounts of data during the pre-design, design and construction, and post-construction phases empowers architects to make data-driven decisions that optimize building performance. This data can provide strategies for material selection, time and energy efficiency, and resource management, ultimately contributing to the realization of Sustainable Development Goals (SDGs) through building design. This research explores the specific applications of artificial intelligence in sustainable building design. To achieve this objective, a systematic literature review and case study analysis were conducted, utilizing academic journals and article reports as primary data sources. Specific keywords were employed to narrow the scope of the research. The analysis involved classifying AI applications and investigating their potential benefits in : 1) analyzing environmental conditions, such as historical and real-time climate data to optimize building orientation, and natural ventilation strategies, 2) facilitating the design process by providing real-time visualization and recommendations for achieving sustainable designs, 3) optimizing building materials and construction efficiency, by analyzing material properties, and providing accurate data during the construction stage to gives broader image on how to build efficiently and 4) simulating building performance, by predicting and doing assessment on the building’s energy consumption and thermal performance, allowing architects to refine design for optimal sustainability. By integrating AI into these workflows, architects can address critical challenges like global warming and climate change by creating high-performing, sustainable buildings. Keywords: Artificial Intelligence, Energy Efficiency, Global Warming, Sustainable Architecture